2022
DOI: 10.1007/s43032-022-00960-9
|View full text |Cite
|
Sign up to set email alerts
|

Human Myometrial and Uterine Fibroid Stem Cell-Derived Organoids for Intervening the Pathophysiology of Uterine Fibroid

Abstract: Uterine fibroids (UFs) (leiomyomas or myomas) are the most common clonal neoplasms of the uterus in women of reproductive age worldwide. UFs originate from myometrium consist of smooth muscle and fibroblast components, in addition to a substantial amount of fibrous extracellular matrix which all contribute to the pathogenetic process. Current treatments are primarily limited to surgical and interventional. Here, we have established a novel and promising organoid model from both normal and patient myometrial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…Transcriptomic analysis of HMGA2hi cells further revealed increased stemness, as evidenced by a significant increase in the expression of another mesenchymal marker, CSPG4 (26), along with enrichment for two stem-related pathways. Several studies have demonstrated the capability of myometrial and fibroid stem/progenitor cells to differentiate into various cell types (26,32,36). However, to our knowledge, no previous reports have investigated whether myometrium and fibroid cells depleted for stem/progenitor cells retain the ability to differentiate into other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analysis of HMGA2hi cells further revealed increased stemness, as evidenced by a significant increase in the expression of another mesenchymal marker, CSPG4 (26), along with enrichment for two stem-related pathways. Several studies have demonstrated the capability of myometrial and fibroid stem/progenitor cells to differentiate into various cell types (26,32,36). However, to our knowledge, no previous reports have investigated whether myometrium and fibroid cells depleted for stem/progenitor cells retain the ability to differentiate into other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…MMSCs formed organoids and showed responsiveness to the core regulatory hormone estrogen with an overall increase in size. Interestingly, MMSC and UFSC developed organoids showed a differential gene expression profile in response to progesterone treatment in terms of progesterone-responsive genes expression [ 67 ].…”
Section: Progesterone Signaling In Uterine Fibroid Pathogenesismentioning
confidence: 99%
“…An increasing amount of evidence supports the hypothesis that LM arises from abnormal stem cells in the myometrial smooth muscle compartment of the uterus [18,19]. Such cells seem to originate from a point mutation in key genes and may present complex histologic features that interfere directly with the diagnosis [20].…”
Section: Introductionmentioning
confidence: 97%
“…Such cells seem to originate from a point mutation in key genes and may present complex histologic features that interfere directly with the diagnosis [20]. Endocrine disruptors and racial or ethnic factors may contribute to genetic alterations in myometrial stem cells [18][19][20][21]. Additionally, these cells are more frequent in Afro-descendant women with LMs than in Caucasians without them [21].…”
Section: Introductionmentioning
confidence: 99%